تأثير العلاج الفيزيائي الصدري على الحالة التنفسية عند الأطفال المصابين بذات الرئة - عيسى مروان; حكيم مأمون; شرف الدين عبد اللطيف (Latakia University Journal -Medical Sciences Series, 2016)
- المقدمة: تقتل ذات الرئة كل عام 2 مليون طفل دون سن الخامسة لتشكل السبب الرئيسي للوفيات في هذه الفئة العمرية. وتعالج بالصادات الحيوية والأكسجين وتقنيات التخلص من المفرزات كالعلاج الفيزيائي الصدري (CPT). يتضمن الـCPT بشكل أساسي عند الأطفال نزح الوضعة والقرع والاهتزاز. - الهدف: يهدف هذا البحث إلى دراسة تأثير العلاج الفيزيائي الصدري (CPT) على الحالة التنفسية عند الأطفال المصابين بذات الرئة. - مواد البحث وطرقه: أجري هذا البحث في مشفى الأطفال الجامعي في دمشق على عينة قوامها خمسون طفلاً واعياً مصاباً بذات الرئة من كلا الجنسين ، تراوحت أعمارهم بين سنة وخمس سنوات. قسمت العينة عشوائياً بالتساوي إلى مجموعتين: المجموعة الضابطة التي تُركت لروتين المشفى، والمجموعة التجريبية التي طُبِّق عليها العلاج الفيزيائي الصدري المكون من نزح وضعي وقرع واهتزاز وذلك لمدة أربعة أيام بحيث استمرت كل جلسة علاج مدة 10 دقائق ثلاث مرات يومياً بفاصل ساعتين بين المرة والأخرى. قُيِّمت الحالة التنفسية لكلتا المجموعتين قبل التطبيق وبعده وقُورنت النتائج، كما وثِّقت مدة بقاء الطفل في المشفى. - النتائج: أظهرت الدراسة تحسناً ذا دلالة إحصائية في الحالة التنفسية عند الأطفال المصابين بذات الرئة الذين أخضعوا للعلاج الفيزيائي الصدري فقد انخفض كل من معدل التنفس، والحاجة اليومية للأوكسجين، وشدة الخراخر التنفسية، ومدة الإقامة في المشفى. كما ازداد معدل تشبع الدم الشرياني بالأوكسجين. - التوصيات: توصي الدراسة بإجراء الـ CPT للأطفال دون سن الخامسة المصابين بذات الرئة أربعة أيام على الأقل من بدء قبول الطفل في المشفى ثلاث مرات يومياً. - Introduction: Pneumonia kills annually about 2 millions of children aged less than 5 years to be the main cause of death at this age group. Pneumonia is treated by antibiotics, oxygen and techniques for releasing secretions as Chest Physical Therapy (CPT). For children, CPT includes essentially postural drainage, percussion and vibration. - Aim: This study aimed to study effect of chest physical therapy on respiratory status among children with pneumonia. - Materials and Method: This study carried at Universal Children Hospital in Damascus, on a sample of 50 conscious children with pneumonia, aged between 1-5 years. The sample was divided randomly to two equal groups: control group that has been left to hospital routine, and study group that has been undergone CPT which consisted of postural drainage, percussion and vibration. CPT has been applied for 4 days as 3 times per day with interval of 2 hours between each time, each CPT session took 10 minutes. Respiratory status has been assessed for both groups before and after applying CPT and then results has been compared, also period of hospital stay has been documented for both groups. -Results: This study demonstrated that there is a statistical improvement in respiratory status among children with pneumonia whose been undergone CPT. That showed by the decreasing of respiratory rate, daily requirements of oxygen, severity of respiratory crackles, and hospital stay; and by the increasing in oxygen saturation. - Recommendation: This study recommended applying CPT for children under 5 years of age with pneumonia for a period of four days as three times per day.